PERBEDAAN FINTECH PEER TO PEER LENDING ANTARA GENERASI X DAN GENERASI Y DALAM MODEL BEHAVIORAL INTENTION DI MANADO - Walangitan, Priskila Gissela Marlia; Lapian, Joyce S.L.H.V; Sumarauw, Jacky S.B (FEB Universitas Sam Ratulangi Manado, 2020)
Abstract: Financial Technology is considered as the development of financial technology in the financial services sector. One of the most interesting types of financial technology (Fintech) is peer-to-peer lending, hence Fintech peer-to-peer lending becomes an alternative choice for loan providers now. This study aims at investigating the difference of Fintech peer-to-peer lending between Generation X and Generation Y in the behavioral intention model in Manado by involving a total sample of 183 respondents who were divided into two groups, namely 88 respondents from Generation X and 99 respondents from Generation Y. This study employed a quantitative causal-comparative study design using the PLS-Multigroup analysis. This study revealed that there were differences in the effect of perceived usefulness, subjective norms, and perceived behavior control on the behavioral intention of use of Fintech peer-to-peer lending between Generation X and Generation Y in Manado City. Meanwhile, perceived ease-of-use, perceived usefulness, and attitude towards a behavior did not have a difference in the effect on behavioral intention of use of Fintech peer-to-peer lending between Generation X and Generation Y in Manado City.Keywords: Perceived ease-of-use, subjective norm, perceived behavior control, perceived usefulness, attitude towards a behavior, the behavioral intention of useAbstract: Financial Technology is considered as the development of financial technology in the financial services sector. One of the most interesting types of financial technology (Fintech) is peer-to-peer lending, hence Fintech peer-to-peer lending becomes an alternative choice for loan providers now. This study aims at investigating the difference of Fintech peer-to-peer lending between Generation X and Generation Y in the behavioral intention model in Manado by involving a total sample of 183 respondents who were divided into two groups, namely 88 respondents from Generation X and 99 respondents from Generation Y. This study employed a quantitative causal-comparative study design using the PLS-Multigroup analysis. This study revealed that there were differences in the effect of perceived usefulness, subjective norms, and perceived behavior control on the behavioral intention of use of Fintech peer-to-peer lending between Generation X and Generation Y in Manado City. Meanwhile, perceived ease-of-use, perceived usefulness, and attitude towards a behavior did not have a difference in the effect on behavioral intention of use of Fintech peer-to-peer lending between Generation X and Generation Y in Manado City.Keywords: Perceived ease-of-use, subjective norm, perceived behavior control, perceived usefulness, attitude towards a behavior, the behavioral intention of use